Funcionamiento familiar y rendimiento escolar en alumnas de tercer grado de secundaria de una institución educativa del Callao - Meza Rojas, Héctor Rigoberto (2010)
The purpose of this research is to understand how it is related the family functioning and school performance. To achieve the study it took a sample of 152 students in the third grade of secondary education, whose ages range between 14 and 17. The research is descriptive, with a correlational design. The questionnaire of the phase III by Olson (1985) was used as an instrument and adapted to our reality for purposes of research. The main results show that there is a relationship between family functioning and school performance, so do the dimensions of family cohesion, and the dimension of adaptability. In conclusion, family functioning is related to school performance.